Letter from E.M. Forster to Alec Randall, June 20, 1932 - http://id.worldcat.org/fast/40913 (1932)
Part of a collection of letters written by E.M. Forster to Sir Alec Randall. They concern, firstly, his trip to Rumania, where he stayed with the Randalls; a tour in France in 1928; and his journey home. Later letters include references to such literary people as Herbert Read, Harold Monro and T.S. Eliot, plus a mention of reading James Joyce's "Ulysses". He also refers to his visit to Africa and his sentiments about the Spanish Civil War and W.W.II. Most of the later letters are signed "Morgan".